Speech Sound Disorders in Early Childhood and Their Impact on Pre-literacy and Literacy Skills: A Systematic Review - Nabila, Choirun Nisa' Mufidatul; Putri, Fara Pradika; Iswinarti (Kirana Publisher (KNPub), 2024)
Children with Speech Sound Disorders (SSD) or a history of SSD are at risk of developing literacy problems later in life. However, there is limited research on SSD children at risk of literacy problems. This systematic review aimed to review 13 international articles on preschool-age SSD and its impact on literacy skills in middle childhood or adolescence. The results of this systematic review show that children who experience SSD in early childhood have poorer early literacy and literacy skills compared to typical children. Based on the literature review, it was found that the severity of speech sound disorder (SSD) does not have a significant correlation with literacy skills. Thus, it can be concluded that children with mild SSD are still at risk of future literacy problems.